Gorillas in the missed (but not the unseen): Reevaluating the evidence for attention being necessary for consciousness. (31st August 2018) - Kozuch, Benjamin
Abstract : The idea that attention is necessary for consciousness (the "Necessity Thesis") is frequently advocated by philosophers and psychologists alike. Experiments involving inattentional and change blindness are thought to support the Necessity Thesis, but they do so only if subjects failing to notice the target stimulus are also not conscious of it. This article uses commonsense phenomenological observations supplemented with empirical data to argue that some subjects failing to notice the target stimulus nonetheless experience its color. Since subjects not noticing the target are commonly assumed to be not attending to it, these scenarios would be instances of consciousness without attention: instead of inattentional and change blindness supporting the Necessity Thesis, they would present counterexamples to it.